Kajian Teknis dan Ekonomis Perancangan Design Kemajuan Penambangan Quarry Batukapur pada Bulan April–Agustus 2017 di Front III B–IV B Bukit Karang Putih PT. Semen Padang - Fikriansyah Ersyad; Dedi Yulhendra; Heri Prabowo (Journals Mining Engineering : Bina Tambang, 2018)
PT. Semen Padang plans to expand mining area, especially in the Front III B-IV B. The limestone production target was planned is 550,000 tons / month. Long-term production target planning for all mining areas in 2017 for limestone is 10,128,000 tons, or increase 12.56 % and silicastone is 1,100,000 tons, or increase 10% from 2016. Production realization achieved in 2016 was only achieved 78.3% for limestone and 71.7% for silicastone. Less optimal achievement of production targets in 2016 due to inappropriate sequence factors, and irregularities in excavation. Planning for limestone mining in Front III B-IV B is based on technical and economical assessmnet in terms of quality and quantity of deposit. In order to maintain the quality of the limestone, it is necessary to know the amount of reserves and the distribution of the quality of limestone in a block model estimated by the geostatistical approach, namely the krigging method. Planning quarry design’s starts from April to August 2017. Combination of loader - hauler that is used to transport limestone is Excavator Komatsu PC 1800-Dumptruck HD 785, while overburden removal use a combination of Excavator Komatsu PC 300-Dumptruck Hino FM260JD. From the design of the quarry in April - August 2017 it was found that in April the overburden stripping was 6,535.71 Bcm and 552,001.89 Tons of limestone, with mining operational costs of $ 160,243. In May the stripping of limestone was reached 569,286.38 Ton, with mining operation cost of $ 162,243. In June, overburden stripping was 5000 Bcm was carried out and 582,636.13 tons of limestone, with mining operating costs reach $ 136,950. In June, overburden stripping was carried out of 29,753 Bcm and 596,955.59 tons of limestone, with mining operating costs of $ 168,989. In August, overburden stripping of 47,000 Bcm was carried out and 579,374.91 Tons of limestone, with mining operating costs of $ 196,683.Keywords:  Production, Mine Planning, Krigging Method, Design Quarry, Operating Cost